A Trincheira dos Porcos na Guerra de Mundos: Ecologia Política da Suinocultura nos EUA, México, Brasil e Argentina - Silva, Allan Rodrigo De Campos [UNESP] (Universidade Estadual de Londrina, 2024)
The globalization of industrial pig farming, driven by modernization, has generated various socio-environmental conflicts in Latin America, pitting local cosmopolitics and cosmotechnics against the commodity production system. This article analyzes the political ecology of landscapes and struggles in pig farming in the U.S., Mexico, Brazil, and Argentina. In the U.S., industrial pig farming disproportionately exploits Black populations, subjecting them to contamination at the edges of CAFOs, while universalizing its practices across Latin America. The effects of the consolidation of pig production on Mexico in the 1990s, Brazil in the 2000s, and Argentina in the 2020s have territorialized disputes inherent to productive integration, subordinating ecologies and peasants to corporations, externalized sanitary risks from the production of giants like China, etc. These places constitute a front in a war of worlds (Krenak, 2017), whose conflicts can be understood through the socio-ecological disputes stemming from the collapse of modernization and nature around the pig trenches, demanding a critical and multispecies resistance network to strengthen territorial struggles.

A globalização da suinocultura industrial, impulsionada pela modernização, tem gerado diversos conflitos socioambientais na América Latina, opondo cosmopolíticas e cosmotécnicas locais ao sistema produtor de mercadorias. Este artigo analisa a ecologia política das paisagens e lutas na suinocultura nos EUA, México, Brasil e Argentina. Nos EUA, a suinocultura industrial explora desproporcional-mente populações negras, submetendo-as à contaminação nas bordas das CAFOs, enquanto universaliza sua prática na América Latina. Os efeitos da consolidação da produção suinícola sobre o México nos anos 1990, o Brasil nos anos 2000 e a Argentina nos anos 2020 territorializaram disputas inerentes à integração produtiva, que subjuga ecologias e camponeses às corporações, externalizaram riscos sanitários oriundos da produção de gigantes como a China, etc. Estes lugares compõem um front em uma guerra de mundos (Krenak, 2017), cuja conflitualidade pode ser compreendida a partir das disputas socioecológicas do colapso da modernização e da natureza em torno da trincheira dos porcos, exigindo uma rede crítica e de resistência multiespécies para fortalecer as lutas territoriais.
Pig Trench in the War of the Worlds: Political Ecology of Industrial Pig Farming in the USA, Mexico, Brazil and Argentina
Keywords: modernization; swine farming; political ecology; collective health; epidemiology; modernização; suinocultura; ecologia política; saúde coletiva; epidemiologia